An Object-oriented Core for XML Schema - Alagic, Suad; Bernstein, Phil (Microsoft, 2008)
This paper presents the first object-oriented interfaces that capture the essence of the structural complexity of XML Schema. We develop two such interfaces: a lightweight object-oriented interface that hides some of the complexity of XML Schema by simplifying the particle and type hierarchies, and a more complete but more complex interface that contains explicit specification of XSD groups. We define a meta level that can store the full details of XSD schemas, such as content models, type derivations for simple and complex types, and identity constraints, which is available to application programmers via reflection. The applicability of the developed interfaces is demonstrated through a collection of complex object-oriented queries.
Revised May 2009